Attribute based encryption in cloud computing: A survey, gap analysis, and future directions. (15th April 2018) - P, Praveen Kumar; P, Syam Kumar; P.J.A., Alphonse
Abstract: Cloud computing facilitates to store and access the data remotely over the internet. However, storing the data in the untrusted cloud server leads the privacy and access control issues in the cloud. The traditional encryption schemes such as symmetric and asymmetric schemes are not suitable to provide the access control due to lack of flexibility and fine-grained access control. One of the prominent cryptographic technique to provide privacy and fine-grained access control in cloud computing is Attribute Based Encryption. In this paper, we comprehensively survey the various existing key policy and ciphertext policy attribute based encryption schemes based on access structure, and multi-authority schemes. Moreover, this review explores more on ciphertext policy attribute based encryption in different aspects such as hidden policy, proxy re-encryption, revocation mechanism, and hierarchical attribute based encryption. Further, this paper compares different ABE schemes based on the features, security, and efficiency. This paper also identifies the suitability of attribute based encryption for practical applications. Finally, this paper analyze the different ABE schemes to find out the research gap and challenges that needs to be investigated further on the Attribute Based Encryption. Highlights: Discuss the fundamental concepts of ABE and its variations KPABE and CPABE based on access structure, and multi-authority. Explore more on CPABE with hidden policy, proxy re-encryption, revocation mechanism and HABE. Analyse the various ABE schemes based on functionalities, security, and efficiency to find the open challenges. Identify the suitable applications and future direction of attribute based encryption in cloud computing.